Migration and the formation of transnational economic networks between Africa and Turkey: the socio-economic establishment of migrants in situ and in mobility. Issue 3 (2nd September 2017) - Suter, Brigitte
ABSTRACT: Turkey is often perceived as a transit place for migrants and refugees from the African continent. While many indeed continue to other countries and the country still precludes official local integration, the past decade has witnessed a growing number of African migrants settling in Istanbul. This article draws attention to the opportunity structures that enable this type of settlement. The article presents the argument that it is the presence of small-scale transnationally embedded traders from the same countries that enable the socio-economic stability of their co-nationals both locally as well as transnationally. The concept that is able to account for this development is establishment in situ and establishment in mobility, which is seen as exactly the definitional barrier between transit and settlement.